UJI AKTIVITAS PENURUNAN KOLESTEROL PRODUK MADU HERBAL YANG BEREDAR DI PASARAN PADA TIKUS PUTIH DIET LEMAK TINGGI - Ariantari, Ni Putu; Chandra Yowani, Sagung; Swastini, Dewa Ayu (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 1 Januari 2010)
The research aims to investigate hypocholesterolemic activity of two marketed herbal honey products for hypocholesterolemia, mentioned as product A and B on Wistar albino rats with hypercholesterolemic diet. Hypocholesterolemic activity test was conducted with Enzymatic Photometric Test CHOD-PAP (Cholesterol Oxidase Phenol Aminoantipyrin) method. The result revealed that product A administered orally to Wistar albino rats with hypercholesterolemic diet, at 0.15 mL/200g BW dose once daily, did not show hypocholesterolemic activity. On the other hand, product B at 0.5 mL/200g BW dose showed hypocholesterolemic activity similar to simvastatin.
Keywords: hypocholesterolemic activity, herbal honey, Enzymatic Photometric Test CHOD-PAP